Diastereoselective synthesis of functionalized spiroindolines via intramolecular ipso-iodocyclization/nucleophile addition cascade reactions of indole-tethered ynones - Bag, Debojyoti; Sawant, Sanghapal D. (Organic and biomolecular chemistry, 2024)
Herein, we describe a highly diastereoselective approach for synthesizing polyfunctionalized spiroindolines from indolyl-ynones involving an ipso-iodocyclization/nucleophile addition cascade. The developed strategy allows the formation of a spirocyclic core and the installation of two functional groups in a single operation. Also this strategy is accompanied by the generation of two C-C and one C-I bonds and two contiguous stereocenters.

Divergent synthesis of unsymmetrical Bis-heteroaryl ketones via base-promoted cascade reactions of 1,2-alkynedione-derived N-propargylic β-enaminones - Bag, Debojyoti; Saini, Sheetal; Rathod, Mahesh S.; Sawant, Sanghapal D. (JOURNAL OF ORGANIC CHEMISTRY, 2024)
Keywords: ASYMMETRIC-SYNTHESIS; heterocycles; intramolecular cyclization; pyrroles

Discovery and biological evaluation of nitrofuranyl-pyrazolopyrimidine hybrid conjugates as potent antimicrobial agents targeting Staphylococcus aureus and methicillin-resistant S. aureus - Saini, Sapna; Reddy, G. Lakshma; Gangwar, Anjali; Kour, Harpreet; Nadre, Gajanan G.; Pandian, Ramajayan; Pal, Sunny; Nandi, Utpal; Sharma, Rashmi; Sawant, Sanghapal D. (RSC Medicinal Chemistry, 2025)
Nitrofuran and pyrazolopyrimidine-based compounds possess a broad antimicrobial spectrum including Gram-positive and Gram-negative bacteria. In the present work, a series of conjugates of these scaffolds was synthesized and evaluated for antimicrobial activity against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA). Many compounds showed MIC values of <= 2 mu g ml-1, with compound 35 demonstrating excellent activity (MICs: 0.7 and 0.15 mu g ml-1 against S. aureus and MRSA, respectively) and safety up to 50 mu g ml-1 in HepG2 cells. Compound 35 also exhibited no hemolytic activity, biofilm eradication, and effectiveness against efflux-pump-overexpressing strains (NorA, TetK, MsrA) without resistance development. It showed synergistic effects with vancomycin (S. aureus) and rifampicin (MRSA). Mechanistic studies revealed that compound 35 exhibits good membrane-targeting abilities, as evidenced by DAPI/PI staining and scanning electron microscopy (SEM). In an intracellular model, it reduced bacterial load efficiently in both S. aureus and MRSA strains. With a strong in vitro profile, compound 35 demonstrated favorable oral pharmacokinetics at 30 mg kg-1 and potent in vivo anti-MRSA activity, highlighting its potential against antibiotic-resistant infections.

Divergent synthesis of 3-formylpyrazolo[1,5-a]pyrimidines and methylene-bridged bis(pyrazolo[1,5-a]pyrimidines) using DMSO as a single carbon synthon - Sikdar, Papiya; Das, Sourav; Saini, Sheetal; Sawant, Sanghapal D.; Bagdi, Avik Kumar (Organic & Biomolecular Chemistry, 2025)
A divergent approach has been explored for synthesizing 3-formylpyrazolo[1,5-a]pyrimidines and methylene-bridged bis(pyrazolo[1,5-a]pyrimidines) using DMSO as a C1 synthon. A library of 3-formylpyrazolo[1,5-a]pyrimidines and methylene-bridged bis(pyrazolo[1,5-a]pyrimidines) has been synthesized using CuOAc and AcOH, respectively. The reaction progressed through a radical pathway. The usefulness of 3-formylpyrazolo[1,5-a]pyrimidines in synthesizing a zaleplon derivative has been demonstrated.